Consumer perceived brand innovativeness: Conceptualization and operationalization. Issue 9 (14th September 2015) - Shams, Rahil; Alpert, Frank; Brown, Mark
Abstract : Purpose: – This paper aims to examine brand innovativeness. While innovativeness has been studied at the product and firm levels, there is little research at the brand level. This paper argues for why this is needed, develops a conceptualization of consumer perceived brand innovativeness (CPBI) from a theoretical perspective and then develops and validates a measure for CPBI. Design/methodology/approach: – Three qualitative studies were conducted to generate an enriched and more detailed understanding of what brand innovativeness means to consumers. Data were collected using free association and open-ended elicitation techniques. Next, a CPBI scale was developed and validated in three quantitative studies. Findings: – The results indicate that innovative brands are related with several interesting core and secondary associations that have not been adequately addressed in previous research. CPBI is conceptualized as a unidimensional construct. Altogether six studies show that the proposed CPBI measure is valid and reliable. Originality/value: – The present study is the first to identify the limitations of product and firm innovativeness conceptualizations with regards to brand innovativeness. It develops a unique and theoretically supported conceptualization and operationalization of CPBI. The first brand concept map for the concept of innovative brands is presented. The results of the studies indicate the measure's ability to successfully predict important consumer behavior variables such as purchase intentions, and to demonstrate superior predictive performance compared with a key related scale in the mobile phone category.